TINJAUAN PELAKSANAAN MOBILE BANKING MUAMALAT DIGITAL ISLAMIC NETWORK (DIN) PADA BANK MUAMALAT KANTOR CABANG MELAWAI - Naurah Salsabila Putri Ayu (2023)
The rapid advancement of information technology greatly affects the banking sector, Mobile banking is a banking service that allows you to do banking transactions easily without having to come to the bank, except to make cash withdrawals. The advantage of mobile banking, customers can make transactions anytime, anywhere without time limits. The Banking Industry needs to actively market mobile banking services. Marketing of mobile banking services is very necessary because all bank customers are expected to take full advantage of mobile banking products. Every bank needs to have a good marketing strategy to achieve its marketing goals. The type of research used is Descriptive Qualitative, where this type of research is research that records, describes carefully a situation or phenomenon in research where this research is limited to revealing a situation based on facts. Bank Muamalat also applies the 7P marketing concept, namely Product, Place, Price, Promotion, People, Process, and Physical Evidence Muamalat DIN Mobile Banking Marketing Strategy carried out by Bank Muamalat, namely using marketing through Social Media and Walk In Customer.